The Influence of Social Media Promotion and Electronic Payment Systems on Purchase Decisions: Case Study from Users of Shopee in Bandar Lampung, Indonesia - Manik, Rionaldo; Soegesti, Dwi Gema (Golden Ratio of Marketing and Applied Psychology of Business, 2026)
This study aims to determine the influence of social media promotion and electronic payment systems on purchase decisions at PT Shopee Indonesia. The population in this study is the community of Shopee users in Bandar Lampung, and the sample takes the entire population using the non-probability sampling method. The results showed that the social media promotion and electronics payment systems partially and significantly affected PT Shopee Indonesia's purchase decisions. The results also show that social media promotion and electronic payment systems simultaneously significantly affect Purchase Decisions At PT Shopee Indonesia. Meanwhile, based on the coefficient of determination (R2) of 0.974 or 97,4%, this shows that 97,4% of the purchasing decision variables can be influenced by social media promotion and electronics payment systems. At the same time, the remaining 2,6% are in other variables not examined in this study.